Karakteristik Komposit Bioplastik pada Perlakuan Rasio Campuran Karagenan-Glukomanan dan Suhu Gelatinisasi - Sitorus, Timothy Ich Sudanton; Harsojuwono, Bambang Admadi; Suwariani, Ni Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 10 No 1 (2022): MaretDO - 10.24843/JRMA.2022.v10.i01.p06, 2022)
This study aims to determine the effect of the carrageenan-glucomannan mixture ratio and gelatinization temperature and their interaction on the characteristics of the carrageenan-glucomannan bioplastic composite and also to determine the carrageenan-glucomannan bioplastic composite on the ratio and gelatinization temperature that produces the best characteristics. This study used a factorial randomized experimental group design. The first factor is the ratio of carrageenan-glucomannan which consists of 6 levels, namely 65:35, 70:30, 75:25, 80:20, 85:15, 60:10 (w/w). The second factor is the gelatinization temperature which consists of 3 levels, namely 70±1, 75±1, 80±1oC. The variables observed in this study were tensile strength, elongation at break, elasticity, thickness expansion, water vapor transmission rate, biodegradation. The resulting data were analyzed for diversity and continued with Duncan's Multiple Comparison test. The results showed that the ratio of the material has a very significant effect on tensile strength, elongation at break, elasticity, and water vapor transmission rate. Gelatinization temperature has a very significant effect on tensile strength, elongation at break, elasticity, thickness expansion, and has a significant effect on the rate of water vapor transmission. The best carrageenan-glucomannan bioplastic composite was obtained at the treatment of carrageenan:glucomannan ratio = 75:25 at a gelatinization temperature of 75±1°C, which only met the standard tensile strength and biodegradation. With a tensile strength of 17,237 MPa, elongation at break 35.2%, elasticity 52.7 MPa, thickness expansion 92.121%, water vapor transmission rate 0.742 g/m2.hour, and biodegradation 6 days Keywords: Bioplastic composite, carrageenan, glucomannan, material ratio, gelatinization temperature